Caracterização do acetato de celulose produzido a partir da acetilação heterogênea do bagaço de cana-de-açúcar - Cruz, Sebastião Francelino da (2002)
In this dissertation the reaction of heterogeneous acetylation was applied to sugar cane bagasse. The product was characterized using: a) Fourier transformed infrared (FTIR) spectroscopy based on the presence of the stretch band of the carbonyl group (around 1740 cm'1), b) wide angle X-rays scattering (WAXD) based on the presence of a maximum in the region of 20 between 5 0 and 10 °, and c) differential scanning calorimetry (DSC) based on the presence of an endothermic peak at approximately 300 °C. From DSC measurements was suggested a new value for the enthalpy of fusion of perfectly crystalline cellulose triacetate. This value is 48 J.g1. The triacetate produced by sugar cane bagasse cellulose acetylation had 67 % of ciystallinity. The acetate produced was cast into fílms and the water flux was measured using the cup technique by Payne. The water flux through fílms of 50 pm was 9.10 ± 0.06) 10’7 gs’ ^m'2. The fílms of cellulose triacetate, with thickness in the range of 20 to 100 pm, had presented two different macrocospic phases, being that the criticai thickness for the phase transition was 50 pm.